Aortic Delamination—A Possible Precursor of Impending Catastrophe - Saeyeldin, Ayman; Zafar, Mohammad A.; Baldassarre, Lauren A.; Mojibian, Hamid; Ziganshin, Bulat A.; Mukherjee, Sandip K.; Elefteriades, John A. (International Journal of Angiology, 2021)
Aortic diameter is a powerful predictor of adverse aortic events, such as aortic rupture or dissection, forming the basis of prophylactic surgical repair criteria. Limited evidence is available regarding the association of aortic wall thickness (AWT) with these adverse aortic events. We present the case and surgical video of a 73-year-old man with chest pain and an increased AWT, who underwent ascending aortic repair and deep hemiarch placement under deep hypothermic circulatory arrest. Surgical pathology demonstrated evidence of aortic delamination and medial separation, indicative of an impending dissection. The patient recovered uneventfully, and his chest pain ultimately resolved after open repair. In this patient, increased AWT was felt to be the precursor to a potential aortic catastrophe.
Keywords: ascending aorta; aortic wall thickness; dissection; rupture; delamination